2016
DOI: 10.1021/acs.biomac.5b01722
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed Silicone–Hydrogel Scaffold with Enhanced Physicochemical Properties

Abstract: Scaffolds with multiple functionalities have attracted widespread attention in the field of tissue engineering due to their ability to control cell behavior through various cues, including mechanical, chemical, and electrical. Fabrication of such scaffolds from clinically approved materials is currently a huge challenge. The goal of this work was to fabricate a tissue engineering scaffold from clinically approved materials with the capability of delivering biomolecules and direct cell fate. We have used a simp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 51 publications
0
50
0
Order By: Relevance
“…The shape stability of the printed features could be significantly enhanced through a second step of covalent crosslinking. For example, through photoinitiated covalent crosslinking, [ 86,91,94,95,102–105 ] strong ionic interactions of alginate with calcium, [ 92,101,106 ] or horseradish peroxidase/hydrogen peroxide crosslinking (H 2 O 2 ). [ 95 ] Burdick and co‐workers reported that despite achieving 3D layer‐by‐layer grid structures using hydrogels crosslinked with only a supramolecular network, the filaments were still fused together when printing multilayers due to the dynamic nature of supramolecular interactions (Figure 3D).…”
Section: Materials Designs For 3d Printabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…The shape stability of the printed features could be significantly enhanced through a second step of covalent crosslinking. For example, through photoinitiated covalent crosslinking, [ 86,91,94,95,102–105 ] strong ionic interactions of alginate with calcium, [ 92,101,106 ] or horseradish peroxidase/hydrogen peroxide crosslinking (H 2 O 2 ). [ 95 ] Burdick and co‐workers reported that despite achieving 3D layer‐by‐layer grid structures using hydrogels crosslinked with only a supramolecular network, the filaments were still fused together when printing multilayers due to the dynamic nature of supramolecular interactions (Figure 3D).…”
Section: Materials Designs For 3d Printabilitymentioning
confidence: 99%
“…Besides UV induced free radical polymerization, the photoinitiated thiol−ene, [ 107 ] thiol‐yne click chemistry [ 108 ] and thiol‐Michael reactions, [ 109 ] which can form a more homogeneous (step‐growth) hydrogel network [ 110 ] compared to that of a free radical polymerized diacrylates were utilized for post‐crosslinking after extrusion. [ 106 ] The strong metal coordination bond between Fe 3+ and COOH − was also employed to encourage fast gelation of the highly viscous linear polymer solutions after extrusion, [ 39,111 ] which significantly simplified the 3D printing process of hydrogels.…”
Section: Materials Designs For 3d Printabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Another advantage of hydrogels is that they can be loaded with chemicals, mimicking ECM-bound regulatory factors in vivo [129,137]. The ECM is known to provide important cues on cells both through its structure and its release of stimulating factors [138].…”
Section: Blood-brain Barrier Models Using Pluripotent Stem Cells 867mentioning
confidence: 99%
“…This results in high-resolution, albeit 2.5D, topographical features which are nevertheless useful in studying the effect of topographical cues in cell culturing [70]. In another recent work [71], a silicone-elastomer/hydrogel interpenetrating network was fabricated by 3D printing PVA filament into a scaffold, pattern transfer into PDMS, and pattern transfer again into silicone-poly(2-hydroxyethyl methacrylate)-co-poly(ethylene glycol) methyl ether acrylate (pHEMA-co-PEGMEA), providing excellent mechanical properties and controlled drug release of the elastomer combined with the biocompatibility and hydrophilicity of the hydrogel.…”
Section: Replicationmentioning
confidence: 99%